1996
DOI: 10.1002/(sici)1097-4644(19960601)61:3<402::aid-jcb7>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Low-molecular-weight variants of osteopontin generated by serine proteinases in urine of patients with kidney stones

Abstract: Osteopontin (OPN) is a multifunctional glycosylated phosphoprotein found in body fluids, including urine, and has been implicated in urinary stone formation. We tested the hypothesis that OPN levels in urine of patients with kidney stones differed from normal individuals. To quantify OPN levels in the urine, we developed an ELISA using a combination of a mouse monoclonal and rabbit polyclonal antibodies raised against a recombinant glutathione-S-transferase-human OPN fusion protein. In a group of 34 patients d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
29
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 12 publications
4
29
1
Order By: Relevance
“…It is therefore more cancer-specific than total Osteopontin. Fragments of the Osteopontin protein excreted into the urine have been used to diagnose ovarian cancer (31) and renal conditions (32). …”
Section: Discussionmentioning
confidence: 99%
“…It is therefore more cancer-specific than total Osteopontin. Fragments of the Osteopontin protein excreted into the urine have been used to diagnose ovarian cancer (31) and renal conditions (32). …”
Section: Discussionmentioning
confidence: 99%
“…Bautista et al (5) found aberrant LMM OPN variants more frequently in SF than normal controls due to increased serine proteases in their urine. We have not observed that urine PF1, ITI, CD59, or calgranulin is susceptible to rapid degradation in the absence of protease inhibitors (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…OPN has been reported to be synthesized by the cells in mineralizing developmental tissues [13,25,26], and several biochemical studies suggest that OPN regulates cell attachment, migration [22,23], and tissue mineralization [4]. In addition, OPN has been reported to play an important role in the calcification that occurs in several pathological conditions in humans, including arteriosclerosis [8,10,12,18,27,28,32] and urinary stones [2,15,20,21,33]. However, no reports exist regarding the involvement of OPN in ectopic calcification in tendon tissues.…”
Section: Introductionmentioning
confidence: 99%